Response to Gonzalez and Özak's (2023) Replication Report - Andrew Dickens (Institute for Replication (I4R), 2023)
Gonzalez and Özak (2023) provide a direct and successful replication of Dickens (2022). Using a reconstructed version of the main independent variables from the same original sources, in addition to an updated version of the source data, the replicators confirm the main finding of the original study. In addition to the replication, Gonzalez and Özak (2023) develop an alternative measure of potential gains from inter-ethnic trade. They use this new measure in an interesting extension that delves deeper into the the specifics of the inter-ethnic trade mechanism proposed and tested by Dickens (2022). In this response, I clarify two minor points about how the original data set was constructed, and contrast the potential shortcomings of the original and alternative measures of inter-ethnic gains from trade.
Additional information: This paper responds to: Gonzalez, Javier, and Ömer Özak. 2023. Replication of Dickens (2022) "Understanding Ethnolinguistic Differences: The Roles of Geography and Trade". I4R Discussion Paper Series No. 62. Institute for Replication.
Keywords: 330